Ingleside - Leslie, Madeline, 1815-1893 (Salt Lake City, UT : Project Gutenberg, 2023)
"Ingleside; or, Without Christ and with Him" by Madeline Leslie is a novel written in the mid-19th century. The book explores themes of faith, hope, and the impact of Christ's presence in daily life, intertwining the experiences of its characters with spiritual reflections. The narrative primarily centers on the lives of a young clergyman, Mr. Angus, and a compassionate young woman named Marion Howard, as they navigate their personal struggles and the lives of those in their community. The opening of the novel introduces readers to the setting and initial tension surrounding Mr. Angus, the newly appointed pastor, who experiences inner turmoil and self-doubt after delivering a heartfelt but sorrowful sermon during his first service. Meanwhile, we also meet Marion, a dedicated individual who is deeply involved in helping the less fortunate. The narrative unfolds with Marion's strong sense of duty and compassion shining through her interactions with those in need, demonstrating a palpable spiritual fervor that resonates throughout the text. As the characters deal with their struggles and aspirations, themes of redemption and the importance of Christian community are poignantly established, setting the stage for their journeys of faith and personal growth. (This is an automatically generated summary.)
Release date is 2023-02-07
Reader24
Keywords: Christian life -- Fiction; Country life -- Fiction; Invalids -- Fiction; Christian fiction, American; Rural churches -- Fiction